PERBAIKAN PELAPORAN KEUANGAN DESA MELALUI INOVASI SISTEM E-VILLAGE BUDGETING DI KABUPATEN BANYUWANGI - Puspita, Dewi Ayu (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2018)
Act No. 6 of 2014 allows village government to be more independent in managing its government system and resources, including its financial and asset management. Village fund allocation sourced from the local government budget of Banyuwangi Regency was increased from Rp 83 billion in 2016 to Rp 148.6 billion in 2017. Village fund from the central government was also increased to Rp 172 billion in 2017. To maintain local budget management, Banyuwangi Government initiated e-village budgeting, a financial application software as an integrated online village budgeting. This research uses descriptive qualitative approach. The units of analysis are Sembulung Village in Cluring District and Jajag Village in Gambiran District, Banyuwangi. Primary and secondary data were sourced from literature study, depth interview, and direct observation using purposive sampling technique. The results show that before implementing e-village budgeting, the village fund management was high in cost and inefficient. The financial statements will automatically be generated by the e-village budgeting system. This system makes financial management easier to perform and is more accountable. As a result, the village fund was used effectively to increase local people’s prosperity and quality of life. Keywords: E-village Budgeting, Financial Reporting, Village Fund, Banyuwangi Regency